Growth kinetics of vitamin C crystals in a batch L(+)-ascorbic acid – methanol – ethanol – water system : size independent growth model approach - Wierzbowska, B. (Array, 2008)
Summary: The experimental data concerning growth kinetics of vitamin C (L(+)-ascorbic acid, LAA) crystals in a seeded and cooling batch mass crystallization process realized in a four–compound: L(+)-ascorbic acid–methanol–ethanol–water system are reported. Influences of initial composition of solution and its linear cooling rate on “average, effective” values of crystal linear growth rate were examined. Small divergences between LAA crystal size distributions (CSDs) data from granulometric analysis and Coulter counter were interpreted theoretically and discussed. Linear growth rates of crystals in a batch crystallizer were acquired with a proposed by Nývlt indirect method, based on the analysis of population density n(L) data in a MSMPR (mixed suspension mixed product removal) crystallizer. Size–independent growth (SIG) kinetics was assumed. It can be concluded, that the largest and the most uniform particles of purified, crystalline vitamin C correspond to higher initial concentration of L(+)-ascorbic acid in a solution and lower cooling rate applied